THE RELATIONSHIP BETWEEN CRYPTOCURRENCY BITCOIN VALUE DETERMINANTS, MONETARY EXPANSOIN AND BITCOIN PRICE: RALS-ADL COINTEGRATION ANALYSIS (Third Sector Social Economic Review, 2023)
Excessive fluctuations in Bitcoin value disrupt the risk-return balance for investors. In this context, the study examines the variables that affect the value of crypto-money Bitcoin and the long-term relationship of these variables with the value of Bitcoin money. As the dependent variable, the monthly change in Bitcoin value for the period 2012-2022, the expansion in the monetary base (M3) of the reserve currencies (US dollar, Euro and sterling) as the independent variable, the long-term interest rates (bond rates) of the same reserve currencies and the gold ounce prices determined. The long-term relationship between the whole of the independent variables and the Bitcoin value of the dependent variable was analyzed with the RALS-ADL Cointegration analysis method. In addition, three different econometric regression models were created for each reserve currency and the effect of independent variables on Bitcoin value were investigated. According to the results of the analysis, it has been revealed that the value of Bitcoin and the independent variables act together in the long run. On crypto currency value; It has been determined that the monetary expansion (M3) in all three reserve money bases has a positive effect, while the gold ounce price and long-term interest rates of the reserve money have a statistically significant negative effect. The findings obtained in the study can contribute to the decision processes of Bitcoin investors to establish the risk-return balance.
Keywords: Cryptocurrency; Bitcoin value determinants; Monetary expansion; Cointegration analysis